Taxes and pensions - Peter Diamond (Center for Economic Studies and ifo Institute (CESifo), 2009)
Pension benefit rules depend on individual history far more than taxes do, and age plays a much larger role in pension determination than in tax determination. Apart from some simulation studies, theoretical studies of optimal tax design typically contain neither a mandatory pension system nor the behavioral dimensions that lie behind justifications commonly offered for mandatory pensions. Conversely, optimizing models of pension design typically do not include annual taxation of labor and capital incomes. After spelling out this contrast and reviewing (and rejecting) zero taxation of capital income based on the Atkinson-Stiglitz and Chamley-Judd results, this article raises the issue of tax-favored retirement savings, a topic where the two subjects come together.
Keywords: H21; H24; H55; 330; pension; income tax; social security; Gesetzliche Rentenversicherung; Rentenfinanzierung; Einkommensteuer; Kapitalertragsteuer; Private Rentenversicherung; Steuerbegünstigung; Theorie; USA